Node.js in practice - Young, Alex R., ....-; Harter, Marc, ....- (Shelter Island : Manning, 2015)
Node.js in Practice is a collection of fully tested examples that offer solutions to the common and not-so-common issues you face when you roll out Node. You'll dig into important topics like the ins and outs of event-based programming, how and why to use closures, how to structure applications to take advantage of end-to-end JavaScript apps, and more.
Keywords: Node.js.; Internet programming